It is given that the sum of a number, its square and its product with another equals 14. Whereas, when the same is done with the other number, that is the other number is squared, multiplied with the other number and finally these two are added to the number itself, it is equal to 28. You must note that none of these numbers can equal 0.
Now, find the sum of the two numbers taken. Suppose, they are x , y find x + y
Note- the sum of the numbers is positive.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First of all, the claim that none of the numbers can equal 0 shouldn't be there... Of course, it is quite obvious that none of them is 0 , since otherwise we would have 0 = 1 4 and/or 0 = 2 8 .
And second of all, x + y can be equal to two different numbers, as we will see later on, so the answer to this question is not unique as you imply.
We have a system of equations: { a 2 + a + a b = 1 4 ⟺ a ( a + b + 1 ) = 1 4 b 2 + b + a b = 2 8
Subtract the first equation from the second: ( b 2 − a 2 ) + ( b − a ) = 1 4 ⟺ ( a + b ) ( b − a ) + ( b − a ) = 1 4 ⟺ ( b − a ) ( a + b + 1 ) = 1 4 ⟹ ( b − a ) ( a + b + 1 ) = a ( a + b + 1 ) ⟺ ( a + b + 1 ) ( b − 2 a ) = 0 ⟺ { b = − 1 − a b = 2 a or
If b = 2 a , by simply substituting this to the initial system of equations we have ⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ { a = 2 b = 4 { a = − 2 3 1 b = − 4 3 2 or
By checking these solutions, we see that both of them are correct.
If b = − a − 1 , we have a 2 + a + a ( − a − 1 ) = a 2 + a − a 2 − a = 0 = 1 4 . Hence we know that b = − a − 1 .
Therefore the only solutions are: ⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ { a = 2 b = 4 { a = − 2 3 1 b = − 4 3 2 or
Which leads us to 2 possible answers: 6 and − 7 .
We have our system of equations:
x + x 2 + xy = 14
y + y 2 + xy = 28
Now we can add them together, and switch the order around a bit to get:
x 2 + y 2 + 2xy + x + y= 42
And we can then factor the x 2 + y 2 in our equation to get :
( x + y ) 2 + (x + y) = 42
And if we replace (x+y) with a to make it simpler and easier to understand, we get
a 2 + a = 42
And then we can subtract 42 on both sides to get 0 on one side
a 2 + a - 42 = 0
Then, we can factor a 2 + a - 42 into (a + 7)(a - 6) and get:
(a + 7)(a - 6) = 0
And through the Zero Product Property, we can conclude that
a + 7 = 0 or a - 6 = 0
So if we solve for a, that means
a = -7 or a = 6
And since a = x + y, and from the question we know that x + y cannot be negative, that means a = x + y = 6
Oh, oops, on line 6 of my answer, I meant to type x 2 + 2xy + y 2 instead of x 2 + y 2 Sorry for the inconvenience :c
This was my second problem today but why didn't my streak go up?
Problem Loading...
Note Loading...
Set Loading...
Simpler solution:
x + x 2 + x y = 1 4
y + y 2 + x y = 2 8
Now add them to get ( x + y ) + ( x + y ) 2 = 4 2 . Solving this we get x + y = 6 , − 7 .
Probably the problem poser should have mentioned the sum is positive.